Five-year clinical performance of monolithic and partially veneered zirconia fixed partial dentures - Labis, Christos; Handermann, Rebecca; Rammelsberg, Peter; Bömicke, Wolfgang (The journal of prosthetic dentistry, 2025)
Statement of problem - The introduction of high-strength zirconia has provided a tooth-colored alternative to metal-ceramics. However, complications such as ceramic chipping have been associated with veneered zirconia. Modifications to zirconia and prosthesis design, such as the omission of occlusal veneering or the avoidance of veneering ceramics through a monolithic design, have been developed to improve clinical outcomes, but clinical data on these developments are limited. - Purpose - The purpose of this study was to generate 5-year prognostic data on the survival, success, and ceramic-related complications of tooth-supported monolithic and partially veneered zirconia fixed partial dentures (FPDs) fabricated from translucent 3 mol% yttria-stabilized tetragonal zirconia polycrystal (Cercon ht; DeguDent GmbH). - Material and methods - A total of 52 participants were enrolled in this observational study and received 68 FPDs (34 monolithic and 34 partially veneered) with 88 pontics. Of these, 58 FPDs were located in the posterior region, 4 in the anterior region, and 6 spanned the canine. The restorations were delivered between November 2011 and June 2016 and were clinically evaluated at fixed intervals. Data were collected until December 2022. The mean observation period of the restorations was 6.0 ±3.0 years (range 0.1 to 10.2); 6.5 ±3.0 years (range 0.6 to 10.2) for monolithic and 5.5 ±2.9 years (range 0.1 to 9.7) for partially veneered FPDs. Kaplan-Meier survival analysis and log-rank tests were performed (α=.05). - Results - A total of 16 FPDs (8 monolithic and 8 partially veneered) failed during the observation period, with biological complications being the most common cause of failure. The cumulative 5-year failure-free survival rates were 89.4% for monolithic and 81.9% for partially veneered (P=.640). The 5-year intervention-free survival rates were 83.7% for monolithic and 68.9% for partially veneered (P=.395). The 5-year ceramic defect-free survival rate was 100% for monolithic and 86.4% for partially veneered (P=.036). - Conclusions - Tooth-supported zirconia monolithic and partially veneered FPDs demonstrated comparable survival and success rates over a 5-year period. However, ceramic complications occurred exclusively in partially veneered FPDs. These findings suggest that monolithic FPDs may offer an advantage in terms of ceramic defect-free survival.
Gesehen am 15.01.2026